Systematic review and case report: Systemic lupus erythematosus with renal tubular acidosis - Prashanth Rawla; Krishna Chaitanya Thandra; John Sukumar Aluru; Sarah Abdel Mageed; Eman Elsayed Sakr; Ghadeer Gamal Elsayed; Mohamed Zidan; Mostafa Ebraheem Morra (Clinical Case Reports, 2020)
Abstract Immune profile assessment—particularly for SLE—and subsequent specific therapy are beneficial in patients with persisting unexplained hyperkalemic or hypokalemic paralysis, especially in case of isolated RTA.